A holistic understanding of cobalt cycling and limiting roles in the eutrophic Lake Taihu. (August 2021) - Fan, Xianfang; Ding, Shiming; Gao, Shuaishuai; Chen, Musong; Fu, Zhen; Gong, Mengdan; Wang, Yan; Tsang, Daniel C.W.
Abstract: Cobalt (Co) cycling is often dominated by its role as a micronutrient in marine, while little is known on its cycling in a shallow eutrophic lake. Monthly sampling was performed in eutrophic Meiliang Bay of Lake Taihu, combining two laboratory control experiments and in situ Co limitation bioassay experiments. The high-resolution dialysis and the diffusive gradients in thin films technique were used to detect dissolved and labile Co, respectively. The positive correlations between dissolved/labile Co and Mn in the sediments for 6 or 7 months demonstrated that the mobility of Co in the sediments was primarily controlled by Mn redox cycling in the field. However, it is unexpected that the dissolved and labile Co only showed a small change over one year irrespective of the significant fluctuation in dissolved/labile Mn, with the concentrations being as low as 1.08 ± 0.22 μg/L and 0.246 ± 0.091 μg/L for dissolved and labile Co in the surface 20 mm sediment, respectively. Cyanobacterial bloom simulation and aerobic-anaerobic-cyanobacterial addition experiments indicated that the level of Co in the sediment-overlying water system was strongly regulated by cyanobacterial uptake, followed by the degradation of Co-enriched cyanobacterial biomass, which offset the influence of Mn redox cycling on Co mobility in the sediment. The significant enhancement of Microcystis spp. biomass by Co addition further indicated that Co was the potential limiting nutrient for cyanobacterial blooms. This work provides new ideas for better management strategies of eutrophication in shallow lakes. Graphical abstract: Image 1 Highlights: The dissolved and labile Co showed little change over one year. Co mobility was mainly controlled by cyanobacterial bloom and Mn redox. Co was the potential limiting nutrient for cyanobacterial blooms.